2012
DOI: 10.1140/epjst/e2012-01589-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of fibre-metal laminates for improved impact performance

Abstract: Abstract. An analytical and experimental investigation into the low-velocity behaviour of GLARE Fibre-Metal Laminates (FMLs) has been performed. A quasi-static approach was developed to estimate the perforation energy absorbed between the constituents of GLARE. The analysis considered contact area increase during perforation and strain rate effect on material properties. Particular attention was paid to the effect of ply-angle orientation and aluminium position. Predicted maximum impact force, maximum displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The energy absorption process in impact time is presented in Figure 5. The energy-time curves are characterized by the stage of energy increase to a maximum value equal to the kinetic energy of the striking body just before its contact with the laminate and the subsequent decrease in energy to a value depending on the material's energy absorption capacity [16,23,24]. It was noticed that as the energy increases, the difference between maximum energy and absorbed energy changes.…”
Section: The Energy Absorption Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The energy absorption process in impact time is presented in Figure 5. The energy-time curves are characterized by the stage of energy increase to a maximum value equal to the kinetic energy of the striking body just before its contact with the laminate and the subsequent decrease in energy to a value depending on the material's energy absorption capacity [16,23,24]. It was noticed that as the energy increases, the difference between maximum energy and absorbed energy changes.…”
Section: The Energy Absorption Processmentioning
confidence: 99%
“…The authors concluded that the thinning of the brittle constituent layer may influence the strain and ultimately affect the mechanical properties. Morinière et al [23] focused on the ply-angle orientation of GLARE laminates and studied energy distribution in individual layers. The authors concluded that the angle variation of the composite plies had a considerable impact on the impact limit, reaching maximum values when fibers were along the diagonals of the plate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cross-ply stacking of fibres along the diagonals of aluminum plate and distribution of aluminum layers between glass layers results in up to 70% higher SEA in GLARE compared to a monolithic aluminum plate (Morini ere et al, 2012b). The cross-ply stacking of fibres along the diagonals of aluminum plate and distribution of aluminum layers between glass layers results in up to 70% higher SEA in GLARE compared to a monolithic aluminum plate (Morini ere et al, 2012b).…”
Section: Fibre Metal Laminatesmentioning
confidence: 99%